Is National Early Warning Score (NEWS) effective in older populations with acute illnesses? - Luke Oakes; Ella Riley; Amna Riaz; Radhiya Bakth; David Goldsmith; Vibhor Barve; Zahra Nejad; Sarah Md Fuad; Kausik Chatterjee (Clinical Medicine)
Introduction: The National Early Warning Score (NEWS) introduced by the Royal College of Physicians in 2012, has been widely adopted across the NHS to monitor patient deterioration. It incorporates vital signs (respiratory rate, oxygen saturation, heart rate, blood pressure, consciousness and temperature) and stratifies risk into low, medium and high categories, each requiring different escalation levels. According to National Institute of Health and Care Excellence (NICE) guidelines (MIB205), a NEWS of ≥5, or a score of 3 in any one parameter, warrants an urgent doctor review.1 However, its suitability for older patients (>65 years), especially in rehabilitation settings, remains under-investigated. This project evaluated adherence to NEWS protocols and assessed the appropriateness of current thresholds for older patients. Materials and Methods: This retrospective observational audit included older patients initially managed at a district general hospital (DGH) before transfer to a nearby rehabilitation unit. Data were extracted from electronic health records (Cerner) between November 2023 and September 2024, including demographics, NEWS values, escalation records, staff responses, length of stay and outcomes. Escalation actions were categorised into three levels for nurses (monitoring, minor intervention and escalation) and four for doctors (no action, monitoring, minor intervention and referral to another specialty). Statistical tests, including Kendall’s tau-B, Chi-square and logistic regression, explored trends and associations with frailty scores and patient characteristics. Results and Discussion: Among 94 patients (mean age 84±7 years), 11,871 NEWS alerts were analysed. Most alerts occurred between days 10 and 20 post-admission, indicating possible delays in identifying clinical decline. 73% of patients were discharged home, 23% to care facilities and 3% died. Nurses primarily continued monitoring (59%), while 9% triggered minor interventions and 32% escalated to medical teams, such as critical care outreach. Frailty significantly influenced nurse escalation: higher frailty scores (6–7) were associated with increased escalation (p<0.001). Conversely, doctors’ responses did not significantly correlate with frailty (p>0.05) and were frequently delayed. While NEWS thresholds showed moderate sensitivity (73–87%), specificity was low (37–48%). Machine learning models highlighted age, oxygen saturation, respiratory rate and temperature as key predictors, suggesting that incorporating frailty could enhance predictive accuracy of nursing escalation (Figs 1 and 2). Conclusion: Current NEWS protocols may be suboptimal for frail older patients, with delays in escalation and inconsistent interprofessional responses. The system’s low specificity and disconnection between nursing and medical teams suggest a need for revised thresholds and clearer communication pathways. Integrating frailty scores and applying machine learning tools could refine risk prediction and guide timely, appropriate interventions. Further research should develop and validate frailty-adjusted NEWS models to support improved patient outcomes.